EVALUATION OF SHORT-TERM CLINICAL OUTCOMES WITH DIFFERENT INHALER DEVICES IN COPD PATIENTS (The Research of Medical Science Review, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory condition and a major global health concern with significant morbidity and mortality. Effective management relies heavily on inhalation therapies, primarily metered dose inhalers (MDIs) and dry powder inhalers (DPIs). However, the comparative effectiveness of these devices remains inconclusive.Objective: This study aimed to compare the short-term outcomes of MDIs and DPIs in reducing acute exacerbations in COPD patients.Methods: A comparative cross-sectional study was conducted at Tertiary Care Hospital of Wah Cantt over six months. Sixty-eight COPD patients, aged 30–80 years, with no prior inhaler use were enrolled and equally divided into two groups: one received MDI and the other DPI, both containing budesonide-formoterol. Baseline demographics were recorded, and patients were followed for 30 days to monitor acute exacerbations. Data were analyzed using SPSS v20 with Chi-square and t-tests applied where appropriate.Results: The frequency of acute exacerbations was significantly lower in the DPI group (14.7%) than the MDI group (38.2%) (p = 0.03). Additionally, DPI users had a longer mean time to first exacerbation (24.6 ± 4.8 days) compared to MDI users (18.9 ± 5.7 days), also statistically significant (p = 0.001). No significant effect modifiers were found in subgroup analysis.Conclusion: DPIs demonstrated superior outcomes over MDIs in reducing and delaying acute COPD exacerbations in the short term. These findings suggest a potential preference for DPI in COPD management, warranting further long-term studies.